PERBANDINGAN DOSIS AIR SIRIH HIJAU (PIPER BETLE L) DALAM MENURUNKAN KADAR GLUKOSA DARAH TIKUS PUTIH (RATTUS NORVEGICUS L) YANG DIINDUKSI ALOKSAN - AYUDYA, RINDA; HARIAJI, ILHAM (LP2MTBM MAKARIOZ, 2024)
Diabetes is a major public health problem. Currently diabetes therapy includes insulin and various other oral anti-diabetic agents which have many side effects. Therefore the discovery of anti-diabetic drugs has shifted the focus to natural medicinal products and plant sources that have minimal side effects. The pharmacological profile of green betel has shown anti-platelet, anti-inflammatory as well as immunomodulatory, gastroprotective, and anti-diabetic activities. Based on this background, the researchers were interested in examining the ratio of the dose of green betel leaf (Piper betle L) in reducing blood glucose levels in white rats induced by alloxan.To determine the ratio of the dose of green betel leaf water in reducing blood glucose levels in white rats (Rattus norvegicus L). This study was experimental with a